Lesson Study as a professional tool to strengthen collaborative enquiry in mentoring sessions in Initial Teacher Education. Issue 5 (20th October 2019) - Næsheim-Bjørkvik, Gro; Helgevold, Nina; Østrem, Sissel
ABSTRACT: There is a strong emphasis on teachers' professional development through collaborative learning, and teachers are expected to be active participants in continuous improvement of practice. It is argued that professional development in teacher education needs to be reconceptualised as learning communities, where enquiry is regarded as an integral part of teaching. Lesson Study is a model for collaborative learning for teachers and aims at understanding the relationship between teaching and pupils' learning, based on systematic enquiry. This paper reports on a study on mentoring sessions in two different conditions in Initial Teacher Education, a Business-As-Usual condition and a Lesson Study intervention. The intervention resulted in more time being spent on mentoring sessions, allowing time to investigate, to predict and to analyse observations made. Based on findings in this study we argue that Lesson Study as a context holds a potential to strengthen collaborative enquiry in student teachers' practicum.